2016
DOI: 10.3389/fcell.2016.00139
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Mechanical Properties of the Developing Cerebral Cortical Proliferative Zone between Mice and Ferrets at both the Tissue and Single-Cell Levels

Abstract: Cell-producing events in developing tissues are mechanically dynamic throughout the cell cycle. In many epithelial systems, cells are apicobasally tall, with nuclei and somata that adopt different apicobasal positions because nuclei and somata move in a cell cycle–dependent manner. This movement is apical during G2 phase and basal during G1 phase, whereas mitosis occurs at the apical surface. These movements are collectively referred to as interkinetic nuclear migration, and such epithelia are called “pseudost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 55 publications
(85 reference statements)
5
46
0
Order By: Relevance
“…We use live imaging of the developing wing disc, in combination with analysis of fixed samples where the cell cycle stage can be unambiguously determined. We confirm through the combinatorial use of live and fixed analysis that in the wing disc, nuclear movement in mitosis, rather than G2 [25,28,29], achieves apical mitotic positioning [26] (Figure 2). Furthermore, our fixed-tissue analysis of mitotic nuclear position recapitulates developmental stage specific differences in mitotic nuclear dynamics ( Figures 1E'-E '', 2 and S1G'-G ''), thereby allowing us to…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…We use live imaging of the developing wing disc, in combination with analysis of fixed samples where the cell cycle stage can be unambiguously determined. We confirm through the combinatorial use of live and fixed analysis that in the wing disc, nuclear movement in mitosis, rather than G2 [25,28,29], achieves apical mitotic positioning [26] (Figure 2). Furthermore, our fixed-tissue analysis of mitotic nuclear position recapitulates developmental stage specific differences in mitotic nuclear dynamics ( Figures 1E'-E '', 2 and S1G'-G ''), thereby allowing us to…”
Section: Discussionsupporting
confidence: 58%
“…We show that mitotic nuclear dynamics change as development progresses and tissue architecture changes (Figures 1 and 2). Previous studies had suggested that tissue density might influence IKNM in the crowded, vertebrate cortex PSE [28,29].…”
Section: C''mentioning
confidence: 97%
See 2 more Smart Citations
“…In three-dimensional environments, cell production via mitosis depends not only on the progression of the cell cycle but also on the movement of cells' nuclei/somata into place for mitosis, making the overall cell-production events highly temporally and spatially dynamic (Keller, Schmidt, Wittbrodt, & Stelzer., 2008;Kurotaki, Hatta, Nakao, Nabeshima, & Fujimori, 2007;Miyata, 2008;Norden, Young, Link, & Harris, 2009;Taverna & Huttner, 2010). Recent studies using slice culture-based imaging and mechanical assessment of developing mammalian brain walls have shown that such dynamic cytogenetic events occur at a very high density under physiologically crowded cellular conditions (Miyata, Okamoto, Shinoda, & Kawaguchi, 2015;Nagasaka et al, 2016;Okamoto et al, 2013;Okamoto, Shinoda, Kawaue, Nagasaka, & Miyata, 2014;Saito, Kawasoe, Sasaki, Kawaguchi, & Miyata, 2018;Shinoda et al, 2018); the studies also show that delays in the cell cycle or nuclear migration in a subpopulation of progenitors can easily lead, in a cell non-autonomous manner, to secondary (more widespread) disorganization of histogenesis (Okamoto et al, 2013;Watanabe, Kawaue, & Miyata, 2018).…”
Section: Introductionmentioning
confidence: 99%